Leadership in Old Testament Narrative: Navigating Divine Calling and the Crisis of Human Authority - Mawikere, Marde Christian Stenly; Hura, Sudiria (EDULEAD: Journal of Christian Education and Leadership, 2025)
This study examines leadership in the Old Testament narrative, focusing on the dynamic tension between divine calling and the crisis of human authority within the framework of God’s sovereignty. Employing a narrative hermeneutic method, the analysis centres on key leadership texts featuring figures such as Jacob, Moses, Gideon, Ruth, David, and King Uzziah, aiming to elucidate how leadership authority is established, challenged, and at times compromised by human ambition. The findings reveal that leadership in the Old Testament is fundamentally a form of stewardship grounded in faithfulness to God’s holiness and submission to His sovereign will, while simultaneously confronting the persistent human tendency towards domination and self-assertion. This study highlights that the successes and failures of these leaders reflect the ongoing tension between divine will and human aspiration, offering pertinent insights for contemporary understandings of leadership within spiritual and ethical contexts. The novelty of this research lies in its comprehensive thematic integration of leadership narratives within the Old Testament tradition, contributing significantly to both theological discourse and practical leadership studies.AbstrakPenelitian ini mengkaji kepemimpinan dalam narasi Perjanjian Lama dengan fokus pada dinamika antara panggilan ilahi dan krisis otoritas manusia dalam konteks kedaulatan Allah. Metode hermeneutik naratif digunakan untuk menganalisis teks-teks sentral, termasuk narasi kepemimpinan tokoh-tokoh seperti Yakub, Musa, Gideon, Rut, Daud, dan Raja Uzia, guna memahami bagaimana otoritas kepemimpinan dibangun, diuji, dan terkadang gagal akibat ambisi manusia. Hasil kajian menunjukkan bahwa kepemimpinan dalam Perjanjian Lama adalah sebuah pelayanan yang bersandar pada kesetiaan kepada kekudusan Allah dan ketundukan pada kedaulatan-Nya, sekaligus menghadapi tantangan dari kecenderungan manusia untuk menguasai dan mendominasi. Studi ini menegaskan bahwa keberhasilan maupun kegagalan para pemimpin tersebut merefleksikan ketegangan antara kehendak ilahi dan aspirasi manusiawi, yang relevan bagi pemahaman kepemimpinan kontemporer dalam konteks spiritual dan etika. Kebaruan penelitian ini terletak pada integrasi tematik narasi kepemimpinan secara holistik dalam tradisi Perjanjian Lama, memberikan kontribusi teologis dan praktis yang signifikan untuk diskursus kepemimpinan masa kini.